Legal Framework for Preventive and Proactive Measures under the Bangladesh of Mental Health Act 2018 - Nower, Anika; Ontar, Md. Morshed Hossain (Padjadjaran Journal of International Law, 2024)
Mental health issues are a growing concern globally, and Bangladesh is no exception. Despite International treaties like Universal Declaration of Human Rights (UDHR), International Covenant on Civil and Political Rights (ICCPR), International Covenant on Economic, Social and Cultural Rights (ICESCR) and Convention on the Rights of Persons with Disabilities (CRPD) , emphasizing the protection of individuals with mental health problems, domestic implementation remains a challenge.. The Bangladesh Mental Health Act, 2018 aims to align with international standards to safeguard the rights of individuals with mental disabilities, yet the law has had some successes in certain areas but has also faced challenges or shortcomings in others. This article analyzes the strengths and weaknesses of the Act, examining how well it adheres to international standards and its impact on the rights and treatment of mentally challenged individuals. The Act's objectives, implementation, and adaptation, focusing on its potential to prevent mental health problems and enforce legal protections.